Modificações químicas de polissacarídeos das algas Lobophora variegata e Dictyota mertensii potencializam suas atividades farmacológicas - Negreiros, Marília Medeiros Fernandes de (2019)
Laminarin (1,3-β-glucan) and fucan (sulfated polysaccharide consisting of sulfated Lfucose) are synthesized by brown seaweeds and have several pharmacological activities described. However, polysaccharides and their activities can be modified, increasing their activities. Thereunto, various techniques are used, such as those called green methods. Given the above, and bearing in mind that the potiguar coast, as well as the northeastern, holds several species of seaweed that have not had their neutral and sulfated polysaccharides completely studied, this work aimed to prospect the main chemical modifications in neutral polysaccharides (laminarins) from Lobophora variegata and sulfated polyscarides (fucanas) from Dicytiota mertensii and verify their farmacological activities, choosing the best modifications for structural characterization. Algae were collected at Pirangi beach, Natal, RN, washed and submitted to proteolysis. Using acetone differential fractionation and molecular mass separation techniques, a 12.4 kDa laminarin was obtained. Physicochemical analysis showed that laminarin (LM) consists only of glucose. Dielectric barrier discharge (DBD), sulfation and galification techniques were used to obtain modified laminarins called LMC, LMS and LMG. The modifications promoted different amounts functional groups inserted: for LMS 1.4% of sulfate was observed, for LMG 1.5% of gallic acid and LMC 11.7% of uronic acids. The modification that most enhanced the antioxidant activities of laminarins was galification, therefore, LM and LMG had their structure elucidated by Nuclear Magnetic Resonance (NMR). The data obtained by NMR analysis corroborate with the previous data proving the structure of laminarin in LM and gallified laminarin in LMG. LM and LMG were not cytotoxic and did not alter the cell cycle of normal canine kidney cells (MDCK) compared to the control. In parallel, it was possible to obtain fucans from D. mertensii after proteolysis and precipitation with methanol. Therefore, silver nanoparticles with fucan called NF were synthesized and called NF. The seventh day was the optimal synthesis day for this particle, whose size was approximately 104 nm. The NF had a round shape very homogeneous size distribution, and stability for 16 months and showed a higher antitumor activity (1mg / mL) compared to fucan. NF also had better antibacterial activity than native fucan and immunomodulatory activities (nitric oxide production and cytokine production) had similar results when compared to NF with native fucans. In general, it we observed that the gallification was the best chemical modification in L. variegata laminarins and the NF potentiated the pharmacological activities of the fucans.